Presurgical cytologic diagnostic test of uterine cavity in ovarian malignant tumor (Faculty of Medicine Universitas Indonesia, 2005)
There are several methods for diagnosing ovarian carcinoma, such as gynecological examination, ultrasonographic examination, and tumor marker examination. However, all these combinations have not yielded high specificity antl sensitivity results. For this reason, it is necessary to perform other examinations to enhance both specificity and sensitivity, and one of them which is of interest to be studied is cytological examination of uterine cavity. By cytological examination of uterine cavity, it is hope that malignant cells originating from ovarian malignant tumor can be found. Discovery of ovarian malignant cells is possible because of peristaltic mechanism in the fallopian tube and negative pressure from uterine cavity, that makes possible the transportation of ovarian malignant cells into uterine cavity through the tube. The objective of this study is to understand the sensitiviry and specificity of cytological examination of uterine cavity in detecting ovarian malignancy. This stucty was a diagnostic test with histological examination as the gold standard, to understand sensitivity, specificity, positive prediction value, and negative prediction value of cytological examination of uterine cavity. A total of 30 cases were included in the study. A nurnber of factors enhanced positive results in cytology of uterine cavity. Those factors were stage and ascites. The more advanced the stage, the greater the positive results, and the presence of ascites increased positive results. On diagnostic test, sensitivity of uterine cavity cytology was 48%, specificity 60, positive predictive value 85.7%, and negative predictive value 18.8% respectively. In conclusion, cytological examination of uterine cavity could be used as one of the methods in assistirtg the diagnosis of ovarian carcinoma. (Med J Indones 2005; 14: 92-6)Keywords : cytology, uterine cavity, ovarian malignant tumor